Incidence and Determinants of Severe Morbidity among HIV-Infected Patients from Rio De Janeiro, Brazil, 2000–2010. Issue 4 (May 2014) - Ribeiro, Sayonara R; Luz, Paula M; Campos, Dayse P; Moreira, Ronaldo I; Coelho, Lara; Japiassu, André; Bozza, Fernando; Veloso, Valdilea G; Chene, Genevieve; Grinsztejn, Beatriz
Background: Reliable information on severe morbidity is essential for identifying priorities for case management and to guide resource allocation within the health sector. Methods: This study describes overall, AIDS- and non-AIDS-related severe morbidity as well as mortality and its determinants in an urban cohort of HIV-infected individuals from a public healthcare institution, the Evandro Chagas Research Institute (IPEC) of the Oswaldo Cruz Foundation, Rio de Janeiro, Brazil. Severe morbid events were defined as all clinical diagnoses listed in hospitalization discharge records; all diagnoses were checked and validated. Generalized estimating equation models were used to estimate incidence rates while adjusting for within-subject correlation. Results: Between 2000 and 2010, 3, 537 patients were followed for a total of 16, 960 person-years (PY) of follow-up. Over the years, annual incidence rate of severe morbid events, AIDS-related events, non-AIDS-related events, and deaths significantly decreased from, respectively, 36.6, 12.9, 23.7 and 3.2 per 100 PY in 2000 to 25.3, 7.9, 17.4 and 1.9 per 100 PY in 2010. Patients' immunological profiles significantly improved with time; 84% of the patients used combination antiretroviral therapy (cART) per year. Immunodeficiency was associated with a higher incidence rate of AIDS- and non-AIDS-related events as well as with the incidence rate of specific non-AIDS events (bacterial infections, toxicities, cardiovascular, renal and respiratory diseases). Conclusions: Our results show that in a middle income country with access to cART, non-AIDS-related events represent an important cause of severe morbidity alongside a still high incidence rate of AIDS-related events.